E-Commerce Transaction in Hello Gold Investment: Islamic Investment Review - Ezahar, Raudzatul Jannah Binti; Shuib, Mohd Sollehudin; Abdul Rahim, Ahmad Khilmy (Asian Business Review, 2020)
With advancing the digital platform, many investment plans were introduced to share the benefits and potential assets invested. This paper aims to seek to understand the e-commerce of gold investment transactions from the context of Shariah. The methodology adopted was interview and document research from the qualitative study. Review of existing literature sheds light on some conditions that must be adhered to in e-commerce gold investment are the four pillars of Islamic contracts consist of contracting parties, the price, offer, and acceptance, and subject matter. Gold investment also has its own standard criteria and regulations that must be fulfilled according to Shariah where the item gold has considered as ribawi item. The finding shows that Hello Gold launched the first online gold platform e-commerce through a new mobile application Smart Saver Plan as an automated 12-months savings plan that helps customers have a saving gold monthly with little effort. The features of e-commerce mobile applications are equipped with easy steps of gold purchasing which contain detailed registration, price, features of the gold specification, and method payment system. Term and condition also adhered to gain the consent of customer engagement in the transaction. Hello Gold is a recognized Shariah-compliant whereby it complies with BNM guidelines. The appraisal of these criteria and features justified the validity of Hello Gold Smart Saver Plan from Shariah review perspectives. The e-commerce of mobile application also meets the Shariah ruling transaction which in turn enhance the level of online trust among Muslim users.